SELF-PERCEPTION IN FULCHER OF CHARTRES: HOW THE CRUSADERS SAW THEMSELVES - Polat, Ziya (Journal of Al-Tamaddun, 2018)
The Crusades shaped world history by changing the relations between Muslims and Christians. They targeted the Muslim World in the Mediterranean basin and lasted approximately two hundred years. The ways the Crusaders perceived themselves had a great influence on the start of their expedition to the East. This article examines socio-psychological aspects of the First Crusade through analysis of the narrative of Fulcher of Chartres. It discusses how the self-perception of the Crusaders motivated them at the start of the First Crusade. It seeks to answer the following questions: How did the Crusaders see themselves, with what mind set did they go on this campaign? Why did they go to the East? How did they position themselves in respect to the Muslims?